Sintesis Sabun Lunak Yang Mengandung Polihidroksi Dari Minyak Biji Kakao (Theobroma cacao,L) - Chairul Saleh; Daniel Tarigan; Rabiatul Adhawiyah Al-Idrus (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
The research about synthesis of Soft Soap Containing polyhydroxy from Cocoa seed Oil, beginning with the manufacture of the polyhydroxy compound wherein the polyhydroxy compound is obtained through a process of epoxidation and hydroxylation by reacting oils cocoa beans with peroxide acetic acids (peroxy acetate was obtained from the reaction of glacial acetic acid with hydrogen peroxide) with an acid catalyst sulfate followed by oxirane ring opening process (hydrolysis) at a temperature of 40-45 oC for 2 hours, the results obtained with the reaction yield of 60 %. In the form of a mixture of soft soap is obtained by saponification of compounds polyhydroxy with Potassium Hydroxide at a temperature 70-75 oC for 1 hour with a yield of 86,45 %. Polyhydroxy compound and soap from the cocoa bean oil was analyzed by FT-IR spectrophotometer. Respectively iodine from the cocoa bean oil 102,93mg I / gram of oil and polyhydroxy compound is 20,21 mg I / gram of oil. HLB of soap Software of oil and polyhydroxy cocoa beans from the cocoa bean oil is determined by titration method and obtained HLB of soft soap from the cocoa bean oil was 8.74 while the polyhydroxy from cacao seed oil is 10,94.